"Counter-Catchwords" in the Codices of the Theban Magical Library. - Cesteros, Miriam Blanco (Symbolae Osloenses, 2024)
This article analyses a practice employed by the so-called Hand C (fourth century AD) of the Theban Magical Library. The practice in question consists of repeating one or more words from the end of one page of a codex at the beginning of the next. The repeated text is called "counter-catchword" in manuscript studies. However, it has not yet described in relation to manuscripts dating from before the Middle Ages. Through other similar scribal practices and some interesting and little-known parallels from the Ptolemaic and Roman periods, an attempt will be made to understand the function of the counter-catchwords in the codices of the Theban Magical Library.